Redescriptions and new species in the ‘Austrosignum–Munnogonium’ complex sensu Just & Wilson (2007), mainly from the Southern Hemisphere (Crustacea: Isopoda: Paramunnidae) - Just, Jean; Wilson, George D.f. (Zootaxa, 2021)
Type material is used to illustrate and redescribe the following species in the paramunnid Austrosignum–Munnogonium complex (classification sensu Just and Wilson 2007): Cryosignum incisum (Richardson, 1908), Cryosignum latifrons (Menzies, 1962) comb. nov., Meridiosignum kerguelensis (Vanhöffen, 1914), Munnogonium falklandicum (Nordenstam, 1933), Munnogonium globifrons (Menzies, 1962), and Munnogonium tillerae (Menzies & Barnard, 1959,—topotypes). In addition, seven new species in the complex are described, Austrosignum pilosum, Austrosignum latum, Cryosignum nordenstami, Meridiosignum convexum, Meridiosignum macquariensis, Munnogonium longicaudatum, and Tethygonium monocuspis. Boreosignum Just and Wilson, 2007 is reported from Australia for the first time as Boreosignum specimens. Keys to species in Austrosignum, Cryosignum, Meridiosignum, Munnogonium and Tethygonium are given. A summary of distribution with a list of all species in the complex including occurrence is presented.